Utilization of Teaching Media in Indonesian Language Textbooks for Grade VII and Their Relevance in Merdeka Curriculum - Eka Sofia Agustina; Siti Asmaul Husna (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Indonesian language learning in Merdeka Curriculum serves not only as a tool for communication but also as a means of critical thinking. This study aims to describe, provide insights, and explain the analysis results of utilizing teaching media in Grade VII Indonesian language textbooks and their relevance to the learning materials in the Merdeka Curriculum. The study employs a descriptive-qualitative design. The stages involved include determining data collection procedures through literature studies, consisting of reading, note-taking, and processing research materials. The analysis of the Grade VII Indonesian language textbooks revealed 86 graphic media elements, categorized as follows: (1) image media, reproducing original forms in two dimensions, such as photographs or paintings, with the largest count of 83 images; (2) chart media, consisting of 2 flowcharts; and (3) schematic media, comprising 1 schematic. However, no data on map media were found in the textbooks. Based on their alignment with the learning materials, the teaching media in the Grade VII Indonesian textbooks are consistent with the curriculum objectives. The variety of teaching media supports the achievement of Phase D in the Merdeka Curriculum, reflecting a transition from basic learning to more complex and structured learning.